Evaluation of Experimental and Registered Soil-Applied Insecticides for Management of Larval Corn Rootworm - Aaron Gassmann; Ben Brenizer (Hello World!, 2024)
The purpose of this study was to evaluate the effectiveness of soil-applied insecticides for management of corn rootworm (Diabrotica spp.) larvae. The insecticides evaluated in this study were: Nurizma at two rates, BAS 450UMI, Capture LFR, Force EVO, Aztec 2.1G and Nurizma paired with TWO.O. The corn used for this study was a hybrid that contained no Bt traits targeting larval rootworm. Nurizma, Capture LFR, Force Evo and Aztec 2.1G are all registered by the EPA and available for management of corn rootworm larvae. TWO.O (Bacillus thuringiensis strain EX297512) is registered by the EPA for enhancing microbial activity in the soil.